2005
DOI: 10.7326/0003-4819-142-5-200503010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Levels and Protection after Hepatitis B Vaccination: Results of a 15-Year Follow-up

Abstract: Hepatitis B vaccination strongly protected against infection for at least 15 years in all age groups. Antibody levels decreased the most among persons immunized at 4 years of age or younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(185 citation statements)
references
References 30 publications
14
162
2
7
Order By: Relevance
“…Many regions and countries that were deemed high-risk for HBV infection have now run routine vaccination campaigns for almost three decades, and follow-up studies now show significantly reduced levels of chronic HBV infection within vaccination age cohorts in regions which include Thailand, Taiwan, and Alaska, amongst others [4][5][6][7].…”
Section: General Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Many regions and countries that were deemed high-risk for HBV infection have now run routine vaccination campaigns for almost three decades, and follow-up studies now show significantly reduced levels of chronic HBV infection within vaccination age cohorts in regions which include Thailand, Taiwan, and Alaska, amongst others [4][5][6][7].…”
Section: General Backgroundmentioning
confidence: 99%
“…After follow-up of universal infant vaccination within these regions, prevalence rates of HBsAg within vaccination age cohorts are now 0.7% and almost 0%, respectively [4,6].…”
Section: Global Usementioning
confidence: 99%
“…1 To control HBV infection, universal neonatal immunisation with the hepatitis B vaccine was introduced more than 3 decades ago, and its efficacy has been reported in many studies that have shown not only a reduction in the prevalence of childhood HBV infection, but also the presence of an anamnestic response that could maintain immunoprotection for many years. [2][3][4][5][6][7][8][9][10][11][12][13][14] Indeed, in Taiwan, following introduction of the vaccine, the incidence of hepatocellular carcinoma (HCC) in children was reduced from 0.54 to 0.20 per 100,000 children aged 6-14 years in those born before versus after the vaccination program. 15 In Hong Kong, selective active-passive hepatitis B immunization was first administered to neonates born to mothers screened positive for hepatitis B surface antigen (HBsAg) from late 1983 to 1988, 16 followed by universal neonatal HBV vaccination from November 1988, 17 and the vaccine has become widely available since.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that anti-HBs titers decline rapidly within the first year and then more slowly after primary immunization, and the higher the antibody levels, the longer the period of protection. 8,9,15,16 The total anti-HBs GMT observed at 1 month and 12 months after the third dose was 375.43 and 40.60 mIU/ml, respectively. There were significant differences among the schedules that showed a significant increase from the 0-1-3 to 0-1-12 schedule at both time points.…”
Section: Discussionmentioning
confidence: 96%